Multi-Access Networking with Wireless Ultrasound-Powered Implants - Chang, Ting Chia (IEEE Biomed Circuits Syst Conf, 2019)
Multi-access networking with miniaturized wireless implantable devices can enable and advance closed-loop medical applications to deliver precise diagnosis and treatment. Using ultrasound (US) for wireless implant systems is an advantageous approach as US can beamform with high spatial resolution to efficiently power and address multiple implants in the network. To demonstrate these capabilities, we use wirelessly powered mm-sized implants with bidirectional communication links; uplink data communication measurements are performed using time, spatial, and frequency-division multiplexing schemes in tissue phantom. A 32-channel linear transmitter array and an external receiver are used as a base station to network with two implants that are placed 6.5 cm deep and spaced less than 1 cm apart. Successful wireless powering and uplink data communication around 100 kbps with a measured bit error rate below 10(−4) are demonstrated for all three networking schemes, validating the multi-access networking feasibility of US wireless implant systems.